IMPACT OF THE COVID-19 PANDEMIC ON TEACHERS’ MENTAL HEALTH: INTEGRATIVE LITERATURE REVIEW - Jacob, Marcelo (Health and Society, 2023)
On December 30, 2019, the Chinese city of Wuhan became the center of an outbreak of the zoonotic Coronavirus disease 2019 – Covid-19. A series of international studies have been researching the emotional repercussions of the COVID-19 pandemic on health professionals, and on vulnerable population groups in general. In Brazil, research on teachers’ health gained proportions from 2006 onwards, and the country currently has several studies on the topic. In national literature, the term “teacher malaise” is related to the illness and psychological suffering of teachers with the observation of a considerable increase in mental disorders. Objectives: Identify and analyze the main impacts of the Covid-19 pandemic on the mental health of basic education teachers, according to national and international literature in Health Sciences and Education. Methodology: integrative review of studies on the impact of the Covid-19 pandemic on mental health. Result and Discussion: The integrative review highlighted 13 studies, whose results point to the impacts of the pandemic on changes in routine, gender issues, family relationships and the mental health of school teachers. Conclusions: Today, 2 years and 8 months after the alert of the first cases of pneumonia in the city of Wuhan in December 2019, the psychological impacts of the pandemic on different segments of society are notorious, therefore after the most critical part it is inferred as the main I challenge the analysis of the frequency with which negative feelings such as sadness, anxiety, depression, hopelessness, among others, have affected the teaching population.